2020
DOI: 10.1177/0961203320913619
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of IL-10 promoter polymorphisms on disease susceptibility in Indian SLE patients

Abstract: Single nucleotide polymorphisms in cytokine genes including interleukin-10 have been described to play a vital role in the overall pathogenesis of systemic lupus erythematosus. However, due to a lack of evidence from the Indian population, this study was conducted to analyse the possible influence of interleukin-10 promoter polymorphisms over the disease susceptibility, serum interleukin-10 level and clinical manifestations of the disease in Indian systemic lupus erythematosus patients. In total, 200 systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…IL-10 is a class of anti-inflammatory cytokine secreted by various cell types, 18 which plays a key role in many inflammatory disorders, including arthritis, SLE, and asthma. 19,20 MiR-106a expression is mainly detected in B cells, T cells, macrophages, and EC cells. 21 Sharma et al 22 found that hsa-miR-106a regulated IL-10 expression via binding to the gene's 3 ′ UTR.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is a class of anti-inflammatory cytokine secreted by various cell types, 18 which plays a key role in many inflammatory disorders, including arthritis, SLE, and asthma. 19,20 MiR-106a expression is mainly detected in B cells, T cells, macrophages, and EC cells. 21 Sharma et al 22 found that hsa-miR-106a regulated IL-10 expression via binding to the gene's 3 ′ UTR.…”
Section: Discussionmentioning
confidence: 99%